Pelatihan Bioecoenzim dan Pupuk Lacuba untuk Mendukung Pengetahuan dan Persepsi Siswa terhadap Pertanian Berkelanjutan di SMA Negeri 1 Sitiotio, Kabupaten Samosir - Adinugraha, Fajar; Sitinjak, Rivaldi; Sunarto Sunarto; Silalahi, Marina; Wahyuningtyas, Riska Septia; Murniarti, Erni; Ratnapuri, Adisti; Agustianto, Wahyu (Universitas 45 Surabaya, 2025)
Agriculture in Samosir Regency has great potential but still faces land degradation, dependence on chemical fertilizers, and low utilization of organic waste. The younger generation’s knowledge of sustainable agriculture remains limited, accompanied by negative perceptions of the sector, while practice-based studies at the high school level are rare. Therefore, this study aims to implement bioecoenzim and Lacuba fertilizer training and examine students’ knowledge and perceptions of these activities. The research was conducted at SMA Negeri 1 Sitiotio, involving 41 eleventh-grade students using a one-shot case study design. Data were collected through observation, documentation, questionnaires, and knowledge tests. The results showed that the training ran effectively, as evidenced by active student participation. Students’ perceptions were in the very positive category, with an average score of 87.97, while their knowledge was in the high category, with an average score of 89.76 (Above Average). Thus, bioecoenzim and Lacuba fertilizer training has proven to have the potential to enhance knowledge and foster positive perceptions among students toward sustainable agriculture. Therefore, expanding the application of bioecoenzim and Lacuba training in other schools is important as a practical environmental education tool to support sustainable agriculture.